MANAJEMEN PENGELOLAAN KURIKULUM SEBAGAI STRATEGI PENCAPAIAN VISI SEKOLAH DI SD PLUS QURROTA A’YUN PURWAKARTA - Wishal Luthfikha; Dyah Wulandari (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
The curriculum is the entire teaching material that is implemented in education. The curriculum in Indonesia has undergone many curriculum changes since independence. The purpose of writing this journal is to find out the management of curriculum management implemented at SD Plus Qurrota A'yun Purwakarta. The research method used is a qualitative method with a descriptive approach. The results and discussion of this study can be concluded that the management of curriculum management at SD Plus Qurrota Ayyun Purwakarta has been implemented well, this can be seen from the process of planning, organizing, implementing, and controlling the curriculum which has been implemented gradually and continuously as an effort to achieve the vision of SD Plus Qurrota A'yun Purwakarta to foster a generation with Qur'anic personality, intelligent, educating, creative and able to participate according to their abilities.